2013
DOI: 10.1186/1471-2350-14-127
|View full text |Cite
|
Sign up to set email alerts
|

The 3′-UTR of the adiponectin Q gene harbours susceptibility loci for atherosclerosis and its metabolic risk traits

Abstract: BackgroundAdiponectin Q is a hormone that modulates several metabolic processes and contributes to the suppression of biochemical pathways leading to metabolic syndrome. Hence, polymorphic changes in the adiponectin Q (ADIPOQ) gene are likely to contribute to metabolic disorders, and consequently lead to atherosclerosis. In the present study, we performed a population-based association study for 8 SNPs in 4646 Saudi individuals (2339 CAD cases versus angiographed 2307 controls) by real-time PCR.MethodsLinkage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
2
0
2
Order By: Relevance
“…A recent study conducted in Saudi population showed this SNP to be associated only with low HDL-C serum levels. Although the authors did not report the rare allele frequency for this polymorphism in their population [ 43 ], demographic data from Saudi Arabia shows 10 % of Afro-Asian ancestry which could explain the presence of this allele in this ethnic group. We hypothesized that this African ancestry-specific allele might be conferring a metabolic protection through higher adiponectin levels and an increased homeostasis of fat deposition in subjects within a normal weight range but that protection or metabolic advantage is susceptible to modification under an obese environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study conducted in Saudi population showed this SNP to be associated only with low HDL-C serum levels. Although the authors did not report the rare allele frequency for this polymorphism in their population [ 43 ], demographic data from Saudi Arabia shows 10 % of Afro-Asian ancestry which could explain the presence of this allele in this ethnic group. We hypothesized that this African ancestry-specific allele might be conferring a metabolic protection through higher adiponectin levels and an increased homeostasis of fat deposition in subjects within a normal weight range but that protection or metabolic advantage is susceptible to modification under an obese environment.…”
Section: Discussionmentioning
confidence: 99%
“…Although this ADIPOQ variant is a silent polymorphism located in intron 1, and based on reports from the Alibaba 2.1 program, it is not involved in any putative transcription binding site [ 58 ]. It has recently been suggested that some organisms possess the ability to selectively use certain codons for transcriptional selection or translational and RNA stability [ 43 ], conferring this SNP a potential regulatory activity.…”
Section: Discussionmentioning
confidence: 99%
“…В проекте UK10K Consortium была показана ассоциация гипертриглицеридемии с редкими вариантами гена ADIPOQ, а учитывая связь гипертриглицеридемии с развитием атеросклероза, можно предполагать и влияние вариантов гена ADIPOQ на его развитие [8,9]. Также показана ассоциация ряда ВНП гена ADIPOQ с уровнем адипонектина [7,[10][11][12][13] и со степенью выраженности атеросклероза [14]. В то же время, имеются данные о различном влиянии одних и тех же ВНП в разных популяциях на уровень адипонектина в крови и развитие СД [7,12,[15][16][17].…”
unclassified
“…Muiya N, et al установили корреляцию ряда ВНП 3'UTR области гена ADIPOQ с метаболическими факторами риска и сердечно-сосудистыми заболеваниями, тем самым показав важность этого локуса гена в патогенезе атеросклероза [14].…”
unclassified